The effect of special strength training on developing biomechanical variables run up, hurdle during tuck (Tsukahara) Round off Back performance on the jump table - Abdel Salam, Zina; Alaa Jaafar, Farah (International Journal of Psychosocial Rehabilitation, 2020)
The strength exercises greatly affect the speed of the motor performance, especially the stage of performing the approximate running and upgrading, where the player needs a force that sheds it at the moment of rise to pass the jumping platform, and these exercises must be built according to real indicators based on scientific results to know the nature of this power of the player and the extent of its impact on The length of the gauntlet step during the moment of the rise to pass the advancement plate, through sweating at the nature of the force falling to the initial wheel the last three steps and hitting the rise plate can be used (Foot scan) to determine this dominant force and correct the foot position and areas of pressure projected in order to develop this strength and thus influence the variables Mechanical and achieve a good performance for this skill. It was studied in order to avoid excessive movements in performance and the dispersion of forces, so the researcher was keen to measure these forces by using a foot scanner and extracting Kinematic variables for the Arab jump skill, especially the approximate running stage and upgrading through video imaging and motor analysis and preparing special exercises to develop these variables in order to solve This problem and the researcher imposed no statistically significant differences between the pre and post tests in the (foot scan) and kinematic indicators and the dominant force of the skill of Tsukahara round off Back tuck (Tsukahara) developed on the jump platform. The research was applied to the research sample on the players of the national team for juniors in the technical gymnastics for ages (11-13) years, whose number is (6) players, and the value of (T) was extracted between the results of the tribal and posttests, and the researcher concluded. The effectiveness of the exercises placed within the training curriculum in improving the approximate running and upgrading according to the indicators (Foot scan) and kinematic in the performance of Round off Back tuck (Tsukahara) on the jumping platform and worked to reduce the deviation of the foot from the true path of the rough run, which helps to save time and effort and reduce Distance and skill development.